English Songs in Vocabulary Learning: Higher-Education Students’ Perceived Views - Faisal; Nadiya Nur Putri (University of Surakarta, 2023)
This survey study investigated students' perceptions of using English songs towards their vocabulary learning. It involved 59 sixth-semester English Language Education Study Program students at a private university in Central Java. Data were collected from a closed questionnaire distributed to the research participants via a Google Form. The quantitatively analyzed questionnaire data demonstrated that the average percentage of the three perceptions indicators – perceived object, sensory organs or receptors, and attention – was 86%, included in the ‘Strongly Agree’ criterion based on the interval measurement. The results mean that the students perceived that English songs could help them learn, acquire, and retain new vocabulary. The results showed that students deemed that English songs could attract their interest in learning vocabulary. Using English songs helped them remember the forms, meanings, and uses of newly acquired vocabulary. The students considered listening to English songs a practical and fun learning method for learning, developing, and retaining vocabulary. Therefore, the results of this study can be used as a consideration for lecturers to use English songs to help students boost their interest and motivation to learn vocabulary; consequently, they can use vocabulary suitably.